Knowledge, attitude and practices of indigenous people towards non-communicable disease in Bera, Malaysia: a community-based study - Abdullah, Fa’iza; A Rahman, Nor Azlina; Kumaran, Viknaswaran; Fazam, Nurnisya; Wong, Chai Eng (Malaysian Medical Association (MMA), 2024)
Introduction: With the current trend of increasing on communicable diseases (NCD), like hypertension, diabetes and dyslipidaemia worldwide and in Malaysia, a comprehensive study is essential to find the local population's knowledge, attitude and practice towards NCD. Little is known about the indigenous people of Orang Asli’s health conditions and health-seeking behaviours towards these chronic diseases. The study aimed to assess knowledge, attitudes and practices (KAP) status towards non-communicable disease and its association with demographic background among Orang Asli adults of the Semelai subgroup in central Pahang, Malaysia. Materials and Methods: A cross-sectional study was conducted among 251 adult Semelai people in Bera district, Pahang. Data was collected through face-to-face interviews to obtain socio-demographic data, KAP towards NCD. Bivariate analysis was performed to test the association between the socio-demographic factor and the KAP score. Results: Among respondents, 57.4% were female, 82.5% were married, and 46.2% completed primary school. The majority were animism believers (83.3%), self-employed (75.3%) and earning less than RM1000 (87.6%). The respondents' ages ranged from 18 to 77, with a mean age of 41.1 (S.D ± 13.9). The prevalence of known type-2 diabetes mellitus (T2DM), hypertension, and dyslipidaemia was 9.6%, 20.7%, and 8.8%, respectively. About 23.1% of respondents have a family history of chronic disease. Regarding KAP parameters, only 12.7% have good knowledge, and 35.5% have good practice in prevention and treatment. However, more than half (59.8%) have a positive attitude towards chronic diseases. This study also showed that higher household income and education levels were positively associated with higher scores of KAP (p < 0.001). Conclusion: This study presented a low-to-moderate percentage of Orang Asli who have good KAP towards NCD. KAP levels were significantly associated with education levels and household income. Hence, improving education and poverty in the Orang Asli community may successively increase the knowledge level, impart a positive attitude towards NCDs, and improve the practice level toward treatment and prevention.